Effect of Silica Fume as Industrial Byproduct on the Stabilization of Kaolin Clay Soil - Zaini, Muhammad Syamsul Imran; Suwito, Anang Rustanto; Hasan, Muzamir; Zolkepli, Muhammad Farhan; Abu Talib, Zaihasra (International Journal of Sustainable Construction Engineering and Technology, 2025)
The utilization of chemical stabilizers for soil stabilization is a method by which the construction sector can minimize its negative effect on the environment. Stabilizing of soft clay remains challenging due to the requirement for costly and ecologically harmful materials such as lime and cement. This research investigates the viability of silica fume (SF), an industrial waste, as an eco-friendly soil stabilizer for kaolin clay soil (KCS). Laboratory tests were conducted to examine the impact of different SF concentrations (2%, 4%, 6%, and 8%) on the physical, mechanical, and strength properties of the soil. The addition of SF as soil stabilizers improved the KCS properties, which led to the declines of liquid limit (32.7%) and plasticity index (4.0%). The optimal moisture content of the stabilized sample reduced to 20.4% while the maximum dry density increased to 1.601 g/cm³ indicating enhanced soil compaction characteristic. After 30 days of curing with 6% SF, the KCS’s unconfined compressive strength (UCS) markedly improved from 13.89 kPa to 25.94 kPa. The results demonstrate that industrial waste materials can enhance soil stabilization efficacy while simultaneously improving the environment, rendering them a viable alternative to traditional soil stabilizers.